Double-balloon Remodeling for Coil Embolization of a Primitive Trigeminal Artery Variant Aneurysm: A Case Report - Takigawa, Tomoji (Centauro S.r.l., 2014)
Here we describe the case of a patient with a wide-necked unruptured aneurysm arising at origin of a persistent primitive trigeminal artery (PTA) variant from the right internal carotid artery (ICA), supplying the territory of the right superior cerebellar artery and the anterior inferior cerebellar artery. To preserve the ICA and the PTA variant, coil embolization of the aneurysm was performed using a double-balloon remodeling technique (HyperForm™ and HyperGlide™ Occlusion Balloon Systems; ev3 Endovascular Inc., Irvine, CA, USA). The association of a PTA variant with an aneurysm is very rare. To our knowledge, this is the first description of the use of coil embolization using double-balloon remodeling to treat a PTA variant aneurysm. This technique permits complete embolization and reduces the risk of cerebral and cerebellar ischemia.s